Using e-Worksheet Integrated with PBL-STEM Activities to Improve Disaster Literacy of Junior High School Students - Sari, Witri Puspita; Abdurrahman, Abdurrahman; Lengkana, Dewi (Jurnal Pendidikan MIPA, 2022)
The purpose of this study was to develop a PBL-STEM-based e-worksheet to improve students' disaster literacy using Microsoft Sway. This study uses the Research and Development (R&D) method with 4d (four-D). The 4D development model consists of 4 stages, namely define, design, develop, and disseminate. The instrument used is a needs questionnaire, test instrument. The results of the study stated that the attractiveness of e-LKPD was 88.20%, convenience was 87.52%, and usefulness was 90.96%. The result of Effect Size on PBL-STEM based e-worksheet on disaster literacy is 0.72 in the high category. PBL-STEM-based e worksheet is used to grow literacy effectiveness, especially earthquake threat materials in areas with an N-gain value of 0.68 and moderately qualified. Teachers and students stated that the use of letters, sentences and language in the e-worksheet was easy to understand, indicating that the PBL-STEM-based e-LKPD used to study the threat of earthquake disasters in areas was interesting, useful and the language used was easy to understand and could improve disaster literacy. junior high school students. Keywords: e-Worksheet, PBL-STEM, disaster literacy, Microsoft Sway. DOI: http://dx.doi.org/10.23960/jpmipa/v23i3.pp882-893